"\\Delta = a_{12}^2 - {a_{11}}{a_{22}} = {( - \\sin x)^2} - 1 \\cdot \\left( { - {{\\cos }^2}x} \\right) = {\\sin ^2}x + {\\cos ^2}x = 1 > 0" - we have an equation of hyperbolic type.
Characteristic equation:
"\\frac{{dy}}{{dx}} = \\frac{{{a_{12}} + \\sqrt \\Delta }}{{{a_{11}}}} = \\frac{{ - \\sin x + 1}}{1} \\Rightarrow y = \\cos x + x + {C_1}"
or
"\\frac{{dy}}{{dx}} = \\frac{{{a_{12}} - \\sqrt \\Delta }}{{{a_{11}}}} = \\frac{{ - \\sin x - 1}}{1} \\Rightarrow y = \\cos x - x + {C_2}"
Let
"\\xi (x,y) = y - \\cos x - x,\\,\\,\\eta (x,y) = y - \\cos x + x,\\,\\,u(x,y) = v(\\xi ,\\,\\eta )"
Then
"{u_x} = {v_\\xi }{\\xi _x} + {v_\\eta }{\\eta _x} = (\\sin x - 1){v_\\xi } + (\\sin x + 1){v_\\eta }"
"{u_y} = {v_\\xi }{\\xi _y} + {v_\\eta }{\\eta _y} = {v_\\xi } + {v_\\eta }"
"{u_{xx}} = \\cos x{v_\\xi } + (\\sin x - 1)\\left( {{v_{\\xi \\xi }}{\\xi _x} + {v_{\\xi \\eta }}{\\eta _x}} \\right) + \\cos x{v_\\eta } + (\\sin x + 1)\\left( {{v_{\\eta \\xi }}{\\xi _x} + {v_{\\eta \\eta }}{\\eta _x}} \\right) = \\\\= \\cos x{v_\\xi } + (\\sin x - 1)\\left( {(\\sin x - 1){v_{\\xi \\xi }} + (\\sin x + 1){v_{\\xi \\eta }}} \\right) + \\cos x{v_\\eta } + (\\sin x + 1)\\left( {(\\sin x - 1){v_{\\eta \\xi }} + (\\sin x + 1){v_{\\eta \\eta }}} \\right) = \\\\= \\cos x{v_\\xi } + {(\\sin x - 1)^2}{v_{\\xi \\xi }} + 2\\left( {{{\\sin }^2}x - 1} \\right){v_{\\xi \\eta }} + \\cos x{v_\\eta } + {(\\sin x + 1)^2}{v_{\\eta \\eta }} = \\\\ = {(\\sin x - 1)^2}{v_{\\xi \\xi }} - 2{\\cos ^2}x{v_{\\xi \\eta }} + {(\\sin x + 1)^2}{v_{\\eta \\eta }} + \\cos x{v_\\xi } + \\cos x{v_\\eta }"
"{u_{yy}} = {v_{\\xi \\xi }}{\\xi _y} + {v_{\\xi \\eta }}{\\eta _y} + {v_{\\eta \\xi }}{\\xi _y} + {v_{\\eta \\eta }}{\\eta _y} = {v_{\\xi \\xi }} + 2{v_{\\xi \\eta }} + {v_{\\eta \\eta }}"
"{u_{yx}} = {v_{\\xi \\xi }}{\\xi _x} + {v_{\\xi \\eta }}{\\eta _x} + {v_{\\eta \\xi }}{\\xi _x} + {v_{\\eta \\eta }}{\\eta _x} = (\\sin x - 1){v_{\\xi \\xi }} + (\\sin x + 1){v_{\\xi \\eta }} + (\\sin x - 1){v_{\\eta \\xi }} + (\\sin x + 1){v_{\\eta \\eta }} = \\\\ = (\\sin x - 1){v_{\\xi \\xi }} + 2\\sin x{v_{\\xi \\eta }} + (\\sin x + 1){v_{\\eta \\eta }}"
Substitute the found values into the original equation:
"{(\\sin x - 1)^2}{v_{\\xi \\xi }} - 2{\\cos ^2}x{v_{\\xi \\eta }} + {(\\sin x + 1)^2}{v_{\\eta \\eta }} + \\cos x{v_\\xi } + \\cos x{v_\\eta } -\\\\ - 2\\sin x\\left( {(\\sin x - 1){v_{\\xi \\xi }} + 2\\sin x{v_{\\xi \\eta }} + (\\sin x + 1){v_{\\eta \\eta }}} \\right) - \\\\- {\\cos ^2}x\\left( {{v_{\\xi \\xi }} + 2{v_{\\xi \\eta }} + {v_{\\eta \\eta }}} \\right) - \\cos x\\left( {{v_\\xi } + {v_\\eta }} \\right) = 0"
"{v_{\\xi \\xi }}\\left( {{{\\sin }^2}x - 2\\sin x + 1 - 2{{\\sin }^2}x + 2\\sin x - {{\\cos }^2}x} \\right) + \\\\ + {v_{\\xi \\eta }}\\left( { - 2{{\\cos }^2}x - 4{{\\sin }^2}x - 2{{\\cos }^2}x} \\right) + \\\\+ {v_{\\eta \\eta }}\\left( {{{\\sin }^2}x + 2\\sin x + 1 - 2{{\\sin }^2}x - 2\\sin x - {{\\cos }^2}x} \\right) + \\\\ + {v_\\xi }\\left( {\\cos x - \\cos x} \\right) + {v_\\eta }\\left( {\\cos x - \\cos x} \\right) = 0"
"\\left( { - {{\\sin }^2}x - {{\\cos }^2}x + 1} \\right){v_{\\xi \\xi }} + \\left( { - 4{{\\cos }^2}x - 4{{\\sin }^2}x} \\right){v_{\\xi \\eta }} + \\left( { - {{\\sin }^2}x - {{\\cos }^2}x + 1} \\right){v_{\\eta \\eta }} = 0"
"\\left( { - 1 + 1} \\right){v_{\\xi \\xi }} - 4{v_{\\xi \\eta }} + \\left( { - 1 + 1} \\right){v_{\\eta \\eta }} = 0 \\Rightarrow {v_{\\xi \\eta }} = 0"
Answer: "{v_{\\xi \\eta }} = 0" , where "\\xi (x,y) = y - \\cos x - x,\\,\\,\\eta (x,y) = y - \\cos x + x,\\,\\,u(x,y) = v(\\xi ,\\,\\eta )"
Comments
Leave a comment